Mucous membrane pemphigoid in a series of 7 children and a review of the literature with particular reference to prognostic features and treatment. - Veysey, E.C.; McHenry, P.; Powell, J.; Crone, M.; Harper, J.I.; Allen, J.; Dean, D.; Wojnarowska, F. (European Journal of Pediatric Dermatology, 2007)
Mucous membrane pemphigoid (MMP) is a rare subepidermal immunobullous disease that predominantly affects the mucous membranes. Typically, lesions heal with scarring, which can result in significant morbidity. It is a disease of the middle aged and elderly, with only single case reports or small series (<5 patients) reported in children. We present a series of 7 children with MMP who were referred to a specialist blister clinic between 1996 and 2006 and perform a review of all 23 previously reported cases, with particular reference to the immunopathological and clinical features, how the disease may differ from that in adults, treatment in this age group and prognostic indicators. Of note, the direct immunofluorescence findings indicate that IgA autoantibodies, either alone or with C3, may be associated with a worse prognosis, in particular severe ocular involvement.